6+18x-5=8x+76-5x

Simple and best practice solution for 6+18x-5=8x+76-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+18x-5=8x+76-5x equation:


Simplifying
6 + 18x + -5 = 8x + 76 + -5x

Reorder the terms:
6 + -5 + 18x = 8x + 76 + -5x

Combine like terms: 6 + -5 = 1
1 + 18x = 8x + 76 + -5x

Reorder the terms:
1 + 18x = 76 + 8x + -5x

Combine like terms: 8x + -5x = 3x
1 + 18x = 76 + 3x

Solving
1 + 18x = 76 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
1 + 18x + -3x = 76 + 3x + -3x

Combine like terms: 18x + -3x = 15x
1 + 15x = 76 + 3x + -3x

Combine like terms: 3x + -3x = 0
1 + 15x = 76 + 0
1 + 15x = 76

Add '-1' to each side of the equation.
1 + -1 + 15x = 76 + -1

Combine like terms: 1 + -1 = 0
0 + 15x = 76 + -1
15x = 76 + -1

Combine like terms: 76 + -1 = 75
15x = 75

Divide each side by '15'.
x = 5

Simplifying
x = 5

See similar equations:

| 1x+2y=5 | | 5x+4+2x=53 | | 2k(k+13)=13 | | 6x+3-4x=21 | | (x+8/12)=1-3/4x | | 9x1+5/18 | | V^6+2v^2+7/v^2 | | 3x+2x+6=41 | | 9x15/18 | | 8p+7p=60 | | 2*0/3=4+y | | 4x+3+3x=7x+3 | | X+X+27+3X-33=764 | | -11.6x=104.4 | | 3x^2+5x-1=7x+7 | | -3/7(m-9)=3+6m | | 13x-2(3x+4)=22 | | 2*0/1=4+y | | x/5=14/35 | | 13x-2(3x+4)=32 | | -(6y+1)-(-5Y-4)=-5 | | 6x-54=3x-12 | | x+0.2x=36 | | 13x-143=6x-10 | | n+6=6-6n | | F^2/4g^3/f^4/8g^4 | | 14s+32=2s | | 15x+x=13x-19 | | 10(x+6)=4(x+27) | | 5+5+5=250 | | 2(x-4)=32-6x | | 800=0.8Y-16r |

Equations solver categories